Development Council Meeting - Percival Patterson (My University, 1997)
File includes several documents related to the Central Inlier Gold Project. It also contains an agenda for a meeting of the Development Council, official correspondence, minutes of the meeting of the Development Council and memoranda. The largest item is the "National Industrial Policy: Review and Assessment of Performance in the First year.
185 pgs. Typescript, letter-sized, in good condition
Keywords: Central Inlier Gold Project -Correspondence; National Industrial Policy: Review and Assessment of Performance; Development Council - Correspondence; National Industrial Policy - Jamaica